Pemberdayaan Masyarakat Pulau Karomah, Sukajadi, Pekanbaru Melalui Program Pengembangan Bimbingan Belajar - Lailaturrohmaniyah; Damitra, Yola; Akila Zahra, Vanisa; Deviyanti Marpaung, Mora; Lorenzo, Mario; R. Indrasaputra; Andriani Claudiah Sitinjak, Cici; Tiodora, Feby; Evlina Jamil, Aisyah; M. Iqbalramadhan; Daud, Afrianto (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2023)
The people of RW 02, Pulau Karomah, Sukajadi District, Pekanbaru, and Riau are less aware of the importance of increasing the potential around them. The potential in this context is in terms of quality human resources that are supported by education in practice. One of the programs that the team focuses on is English Tutoring. This program aims to conduct superior, productive, and competitive Human Resources and increase children's motivation to pursue education to compete in the future. The enthusiasm of the children who participated in the tutoring program and the support from the surrounding community were the result of the implementation of this program.